Infestação da cigarrinha-das-raízes (Mahanarva spp.) (Hemiptera: Cercopidae) em cana-de-açúcar e planejamento amostral em diferentes formas da paisagem - Revoredo, Thais Tanan de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The landscape ecophysiology may indicate which abiotic factors may favor insect pest population. This was already evidenced in Europe. The hypothesis is that the landscape can be considered to plan the control of froghopper in the sugarcane industry. The aim of this study was to determine the influence different landscape ecophysiologies on the infestation of Mahanarva spp.in sugarcane. Scouting data collected in november 2011 and 2012 from 110 areas of São Paulo State Northern region and november of 2010 to 2013 from 294 areas of Minas Gerais State Southwestern region were analyzed. The landscape form in which the areas were located was classified as concave (CC) or convex (CX). It was also evaluated the relationship between levels of froghopper infestation and proximity to the river. Data of infestation in each form of landscape were subjected to analysis of variance using mixed models. The values of the coefficient of variation and error were used to calculate the required number of points to sample for the CC and CX forms. The infestation of froghopper was not greater in areas closer to the river when compared to more distant areas. The initial infestation of nymphs is higher in the concave shape (10.58 and 0.43 nymphs m-1) than in the convex shape (5.03 and 0.37 nymph m- 1) for the northern region of São Paulo State and southwestern region of Minas Gerais State, respectively. The sample planning indicates that for areas within concave-shaped landscapes it is necessary 2 points for nymph evaluation (1 m h-1) whereas for convex-shaped forms 3 observations are necessary

A ecofisiologia da paisagem pode indicar quais fatores abióticos podem favorecer as populações de insetos-praga. Isso já foi evidenciado na Europa. A hipótese é que a paisagem pode ser considerada no planejamento de controle da cigarrinha-da-raiz no setor sucroenergético. O objetivo do estudo foi determinar a influência de diferentes ecofisiologias da paisagem na infestação de Mahanarva spp. em cana-de-açúcar. Avaliações realizadas em novembro de 2011 e 2012 obtidas de 110 áreas na região norte do Estado de São Paulo e em novembro de 2010 a 2013 obtidas de 294 áreas no sudoeste do Estado de Minas Gerais foram analisadas. A forma da paisagem em que as áreas estavam inseridas foi classificada como côncava (CC) e convexa (CX). Também foi avaliada a relação entre a infestação de cigarrinha-das-raízes e o rio. Os dados de infestação em cada forma de paisagem foram submetidos à análise de variância utilizando modelos mistos. Os valores do coeficiente de variação e erro foram utilizados no cálculo do número necessário de pontos para observação das formas CC e CX. A infestação de cigarrinhas-das-raízes não é maior em áreas próximas do rio quando comparadas as áreas distante do rio. A infestação inicial de ninfas é maior na forma côncava (10,58 e 0,43 ninfas m-1) do que na forma convexa (5,03 e 0,37 ninfas m-1), para o norte do estado de São Paulo e sudoeste de Minas Gerais. O planejamento amostral indica que para as áreas presentes na forma côncava são necessárias 2 pontos de observação de ninfas (1 m ha-1) enquanto para as áreas na forma convexa são necessárias 3 observações
Keywords: Ecofisiologia; Relevo; Umidade; Amostragem; Cigarrinha (Inseto); Entomology